Effects of object working memory load on visual search in basketball players: an eye movement study - Qing Nian; Wenping Lu; Ying Xu (BMC Psychology, 2023)
Abstract Background Working memory may affect the athletes’ visual search ability. Objective: This study aimed to examine the differences in the performance of visual search tasks among basketball players of varying sport levels, considering the influence of different object working memory loads. Method: This study recruited forty-two participants who were divided into three groups based on the classification of elite athletes: competitive elite, semi-elite, and novice. Results: Objective working memory load significantly impacts the accuracy of visual search, reaction time, and gaze fixation in basketball players. In the visual search task of the basketball sports scene, the inclusion of object working memory load led to a significant decrease in the accuracy of visual search, a significant increase in reaction time, a significant increase in the number of fixation points, and a more complex gaze trajectory. In a visual search task with object working memory load, the difference in reaction time between basketball players of different sport levels was observed during the search initiation time and scanning time, with higher sport levels associated with shorter reaction times. The effect of object working memory load on the eye movement phase of visual search varied among basketball players of different sport levels. For the novice group, the effect was on the reaction time during the verification phase, while for the semi-elite and competitive elite groups, the effect was on the reaction time during the scanning phase. Conclusion: The effect of object working memory load on visual search varied among basketball players of different sport levels.